Waste Management Status of Shrimp Processing Plants of South and South- West Region of Bangladesh (Journal of Environmental Science and Natural Resources, 2019)
The study was carried out on the present status of shrimp processing plant’s waste management in Bangladesh. A detailed survey was conducted during February to May, 2013 in order to collect some basic information on the present status of shrimp waste management at shrimp processing plants through questionnaire interview on the various parameters. Information was collected from 52 plants of Khulna, Chittagong and Cox`s bazaar region. All collected information were accumulated, analyzed and are presented in graphs, figures and tables. The study had revealed that about 671.84MT of shrimp was purchased in 52 plants in a day and from which 248.8 MT of waste product was produced during processing. The study results showed that about 80% of the plants sell their waste products and rest of the plants discharged their wastes into river (63.50%) and 91.42% of the plants treated the waste water before discharge. Based on the obtained results from this study, it could be suggested that shrimp waste can be used further in different ecofriendly ways.J. Environ. Sci. & Natural Resources, 11(1-2): 73-81 2018